Manga reading on paper vs. digital devices: Prospective effects on core and supportive integration processes in the brain - Keita Umejima; Yuki Sunada; Kuniyoshi L. Sakai (PLoS ONE, 2026)
Reading on paper reportedly improves story comprehension compared to its digital version, although the underlying neuroscientific mechanisms remain unclear. We used a format of Japanese manga stories as visual narratives told in halves, each of which depicted the same events from the different perspectives of two protagonists. We examined how the medium used to read the first halves , either on a paper book (Paper preparatory condition) or on an electronic tablet (Tablet preparatory condition), facilitated reading of the second halves for the memorized stories, which they read on an electronic display with continuous empathy ratings. Magnetic resonance scanning was conducted during the latter reading and during answering two sets of questions: Set 1 that could be answered after reading the first half alone, and Set 2 that required comprehension from both halves. Behavioral results showed prospective effects of reading manga stories on a paper book or an electronic tablet, such that the response times were prolonged in Set 2 for the Tablet condition. By comparing the results of Sets 1 and 2 with correct answers for each story, we found significant response time differences for the Tablet condition alone. Moreover, for the Paper condition, activations in the left frontal regions significantly decreased while reading the second halves, and those in the right frontal regions also decreased in Set 1. Furthermore, core left frontal activations were highest in Set 2 for the Tablet condition, while supportive right frontal activations correlated with individual accuracy rates in Set 2 for the Tablet condition, indicating that excessive integration processes support improved performances required by correct answers. The present results demonstrate stronger prospective effects of reading on paper books, such that linguistic and narrative-structural integration processes are facilitated and led to saved excessive activations.